The reformation - Hughes, Philip (Burns & Oates, 1957)
Contents: The reformation changed the entire course of European history. This book is a masterpiece of historical writing that in one volume reduces the turbulent issues, and complex cross-currents of the Reformation to one lucid, coherent account. Mgr Hughes examines first the background to the Reformation-the laxity, often the corruption, that resulted in the demand for reform of the Church. He brings out too a less known but vitally important element: the efforts to reform the Church from within that were beginning to bear fruit before the advent of Luther.